Limb Salvage via Surgical Soft-tissue Reconstruction With Ovine Forestomach Matrix Grafts: A Prospective Study - John Lawlor, DPM; Brandon A. Bosque, DPM; Christopher Frampton, PhD; D. Adam Young, PhD; Patrick Martyka, DPM (Plastic and Reconstructive Surgery, Global Open)
Background:. Complex and chronic lower extremity defects present a surgical challenge and can progress to eventual amputation if closure is not achieved. In addition to morbidity and mortality, these defects have a significant impact on patient quality of life and represent a substantial cost burden to the healthcare system. Ovine forestomach matrix (OFM) grafts are an advanced tissue scaffold option to supplement the surgical reconstruction ladder and may augment limb preservation in cases of complex lower extremity defects. Methods:. A prospective observational study enrolled 130 complex lower extremity reconstructions that received OFM as part of surgical management. Granulation tissue formation, defect closure, and postoperative complications were assessed up to 1 year postoperatively to evaluate the outcome of OFM grafts for limb salvage via surgical reconstruction. Results:. Participant demographics and defect characteristics were reflective of a real-world inpatient population with complex and chronic defects. Despite complexity of the defects, no postoperative infections or major amputations were reported. The median time to complete granulation tissue coverage and fill was 30.0 days (95% confidence interval, 26.9–33.1) and the median time to complete defect closure was 127.0 days (95% confidence interval, 110.5–143.5). At 180 days, a 62% incidence of healing was achieved with a median product application of 1.0 (interquartile range, 1.0–1.0). Conclusions:. OFM-based grafts supported successful coverage of lower extremity defects in a real-world cohort with known risk-factors for amputation. Achieving successful closure with minimal complications, and often in a single application, suggests utility of OFM as a cost-effective adjunct in lower extremity reconstruction.